2017
DOI: 10.1016/j.jebo.2016.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Bowling alone or bowling at all? The effect of unemployment on social participation

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 74 publications
4
21
1
1
Order By: Relevance
“…In social-cultural terms, unemployment is considered a deviation from the norm in societies that value work (Carroll, 2007;Helliwell & Huang, 2014). It has also been found to negatively impact people's ability to engage in leisure and social activities, the formation of interpersonal relationships, childbearing, and family development (Choudhury, 2017;Kunze & Suppa, 2017). In this direction, it has been posited that whereas being unemployed may relate to low psychological wellbeing, it is the social norm that may explain the differences in psychological wellbeing among the unemployed and other members of society (Helliwell & Huang, 2014).…”
Section: Employment Status Ambiguity and Psychological Wellbeingmentioning
confidence: 99%
“…In social-cultural terms, unemployment is considered a deviation from the norm in societies that value work (Carroll, 2007;Helliwell & Huang, 2014). It has also been found to negatively impact people's ability to engage in leisure and social activities, the formation of interpersonal relationships, childbearing, and family development (Choudhury, 2017;Kunze & Suppa, 2017). In this direction, it has been posited that whereas being unemployed may relate to low psychological wellbeing, it is the social norm that may explain the differences in psychological wellbeing among the unemployed and other members of society (Helliwell & Huang, 2014).…”
Section: Employment Status Ambiguity and Psychological Wellbeingmentioning
confidence: 99%
“…Finally, results may suffer a endogeneity bias, e.g., lowering social participation may precede the unemployment spell or individuals may adapt to deprivation in social participation during their unemployment spell. However, Kunze and Suppa (2017) find little evidence in support of these possibilities.…”
Section: Regression Analysesmentioning
confidence: 90%
“…Like social or legal norms, the accessibility of places can affect fairly directly the achievement of social participation-largely independent of resources. Social norms may, however, also operate in more subtle or unconscious ways, e.g., through stigmatisation, which may induce behavioural responses (e.g., Kunze and Suppa, 2017). 13 An outcomebased measurement allows us to investigate these mechanisms more carefully.…”
Section: Selected Features and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, unemployment has been found to be associated with higher levels of loneliness than average (Peplau & Perlman 1982;Moisio & Rämö 2007). Further, previous studies have demonstrated how during unemployment individuals tend to have lower levels of social participation, and withdraw from public activities into private relationships (Dieckhoff & Gash 2015;Kunze & Suppa 2017).…”
Section: Introductionmentioning
confidence: 99%